(untitled) (Czech Journal of International Relations, 1997)
Bohemia, Moravia and Silesia are old cultural territories, whose formation was heavily influenced by Western influence from the beginning of their Slavic history. Ethnic Germans, partly invited by the Czech rulers, partly immigrated to our territory on their own initiative, were naturally expansive as a result of domestic "overpressure" to people. In the Czech lands, they eventually accounted for approximately 30% of the census population (the share of territory dominated by Germans was approximately the same, but this territory was more sparsely populated, as many Germans lived in inland cities). And the Czechs themselves, thanks to the centuries-long, mainly "inland" coexistence, have a considerable share (apparently according to the share of German names in the population, which is the opinion of J. Pekař,1 who called this process Czechization) of "German blood" (to a lesser extent, of course the reverse also applies). After the expulsion of the Germans, this "biological Germanization" undoubtedly weakened, however, the share of Czech-Slovak and Czech-Roma marriages and children born from them increased substantially.